Benralizumab's anti-eosinophil efficacy may be decreased by impaired NK cell activity. Issue 4 (7th April 2022) - Poznanski, Sophie M.; Portillo, Ana; Mukherjee, Manali; Bhalla, Anurag; Son, Kiho; Ashkar, Ali A.; Khalidi, Nader; Nair, Parameswaran
We read with interest the report by Dagher et al. [1] of a novel anti-eosinophil action of benralizumab. Benralizumab was shown to induce eosinophil apoptosis by a macrophage-derived tumour necrosis factor (TNF)-induced caspase 3/7 activation, and this was amplified by interferon-γ (IFN-γ) secreted from natural killer (NK) cells. Indeed, in patients with severe asthma, including those who are dependent on daily systemic glucocorticosteroids for asthma control, benralizumab effectively depletes sputum eosinophils [2]. Although no direct head-to-head comparisons have been made, eosinophil suppression is likely to be greater than with the currently approved dose of mepolizumab [3], leading to greater clinical efficacy [4]. However, there may be instances when the anti-eosinophil activity of benralizumab may be impaired due to decreased NK cell numbers or activity that are described in patients with severe asthma on high doses of glucocorticosteroids [5]. Although likely to be exceedingly rare, impaired ADCC due to NK cell dysfunction needs to be considered as one of the reasons, along with the development of anti-drug neutralising antibodies, for impaired anti-eosinophil activity of benralizumab https://bit.ly/3nxeFVg